An Ultraviolet Thermally Activated Delayed Fluorescence OLED with Total External Quantum Efficiency over 9%. Issue 32 (2nd July 2020) - Luo, Yanju; Li, Shuaibing; Zhao, Yihuan; Li, Chuan; Pang, Zhenguo; Huang, Yan; Yang, Minghui; Zhou, Liang; Zheng, Xujun; Pu, Xuemei; Lu, Zhiyun
Abstract: Owing to the difficulty in acquiring compounds with combined high energy bandgaps and lower‐lying intramolecular charge‐transfer excited states, the development of ultraviolet (UV) thermally activated delayed fluorescence (TADF) materials is quite challenging. Herein, through interlocking of the diphenylsulfone (PS) acceptor unit of a reported deep‐blue TADF emitter (CZ‐PS) by a dimethylmethylene bridge, CZ‐MPS, a UV‐emissive TADF compound bearing a shallower LUMO energy level and a more rigid structure than those of CZ‐PS is achieved. This represents the first example of a UV‐emissive TADF compound. Organic light‐emitting diode (OLED) using CZ‐MPS as the guest material can emit efficient UV light with emission maximum of 389 nm and maximum total external quantum efficiency (EQEmax ) of 9.3%. Note that this EQEmax value is twice as high as the current record EQEmax (4.6%) for UV‐OLEDs. This finding may shed light on the molecular design strategy for high‐performance UV‐OLED materials. Abstract : The first example of a UV‐emissive thermally activated delayed fluorescence emitter, namely CZ‐MPS, is demonstrated successfully. An organic light‐emitting diode using CZ‐MPS as the guest material can emit efficient UV light with an emission maximum (λEL ) of 389 nm as well as a record‐breaking total external quantum efficiency (EQEmax ) of 9.3%.